ANALISIS PENGARUH TRANSFER PRICING, THIN CAPITALIZATION, DAN TAX HEAVEN UTILIZATION PADA PENGHINDARAN PAJAK PERUSAHAAN MULTINASIONAL - Rizky Nurdiansyah, (2022)
Tax avoidance by multinational corporations has been at the top of the international tax policy agenda since the global financial crisis in 2008. This level of tax evasion raises concerns that large multinational corporations pay very low effective tax rates. This study is a quantitative study that has the aim of examining the relationship between disclosure of transfer pricing, thin capitalization, and tax heaven utilization on tax avoidance. This study uses secondary data from multinational companies listed on the Indonesia Stock Exchange from 2018 to 2020. The sampling criteria were taken using the purposive sampling method which was obtained with a total of 136 samples. The sample data was obtained from the Indonesia Stock Exchange (IDX). Hypothesis testing in this study using multiple linear regression models. The model was processed and tested using Microsoft Excel and STATA software. The result of this research is the disclosure of Transfer pricing has no effect on the practice of Tax Avoidance. Thin capitalization has no effect on the practice of Tax Avoidance. Tax heaven utilization has a positive effect on the practice of Tax Avoidance.